2022
DOI: 10.1186/s13195-022-00998-6
|View full text |Cite
|
Sign up to set email alerts
|

The retinal ganglion cell layer reflects neurodegenerative changes in cognitively unimpaired individuals

Abstract: Background To evaluate a wide range of optical coherence tomography (OCT) parameters for possible application as a screening tool for cognitively healthy individuals at risk of Alzheimer’s disease (AD), assessing the potential relationship with established cerebrospinal fluid (CSF) core AD biomarkers and magnetic resonance imaging (MRI). Methods We studied 99 participants from the Valdecilla Study for Memory and Brain Aging. This is a prospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…An increasing number of studies have investigated whether retinal neuronal measurements are associated with brain measurements at various stages of AD. The findings are inconsistent, with some studies finding an association between retinal and brain measurements (Jorge et al, 2020; López-de-Eguileta et al, 2022; Mauschitz et al, 2022; Mejia-Vergara et al, 2021; Méndez-Gómez et al, 2018; Mutlu et al, 2018, 2017; Shi et al, 2020, 2019; Uchida et al, 2020), some finding no association (Casaletto et al, 2017; den Haan et al, 2019), and others with inconclusive results (Donix et al, 2021). However, methodological differences may explain some of this inconsistency—systematic differences between OCT or MRI devices across manufacturers and models, choice of parameters and settings, and the wide range of measurements which can be acquired from each of these technologies make comparison across studies difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have investigated whether retinal neuronal measurements are associated with brain measurements at various stages of AD. The findings are inconsistent, with some studies finding an association between retinal and brain measurements (Jorge et al, 2020; López-de-Eguileta et al, 2022; Mauschitz et al, 2022; Mejia-Vergara et al, 2021; Méndez-Gómez et al, 2018; Mutlu et al, 2018, 2017; Shi et al, 2020, 2019; Uchida et al, 2020), some finding no association (Casaletto et al, 2017; den Haan et al, 2019), and others with inconclusive results (Donix et al, 2021). However, methodological differences may explain some of this inconsistency—systematic differences between OCT or MRI devices across manufacturers and models, choice of parameters and settings, and the wide range of measurements which can be acquired from each of these technologies make comparison across studies difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated these associations in cognitively unimpaired individuals, finding associations between retinal layers including the RNFL and GC-IPL and a number of structural brain measures, most commonly hippocampal volume (Chua et al, 2021; López-de-Eguileta et al, 2022; Shi et al, 2020), but also the lingual gyrus (Shi et al, 2020) and grey and white matter volumes (Chua et al, 2021). A recent study found correlations between RNFL, GC-IPL, and other retinal thickness measures with a large number of cortical thicknesses and volumes, in participants both with and without increased familial and genetic risk for AD (López-Cuenca et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted this analysis with volunteers of the 'Valdecilla Cohort for the study of memory and brain aging' from the Memory Unit of the Marqués de Valdecilla University Hospital [10,11]. The Valdecilla cohort is designed to better understand the preclinical phases of AD.…”
Section: Participantsmentioning
confidence: 99%
“…Recent studies have investigated these associations in cognitively unimpaired individuals, finding associations between retinal layers including the RNFL and GC-IPL and a number of structural brain measures, most commonly hippocampal volume, 21,32,33 but also the lingual gyrus 33 and grey and white matter volumes. 21 A recent study found correlations between RNFL, GC-IPL, and other retinal thickness measures with a large number of cortical thicknesses and volumes, in participants both with and without increased familial and genetic risk for AD.…”
Section: Introductionmentioning
confidence: 99%